Transferências linguístico-culturais em An invincible memory de João Ubaldo Ribeiro: a autotradução de palavras sufixadas por -inho à luz da estilística de corpus - Silva, Pedro Paulo Nunes da (2020)
Viva o povo brasileiro was translated into several languages, such as, German, Dutch, Swedish, French, and Spanish. However, into English, the author himself translated into this language, therefore, a self-translation. The novel was published in 1984 and its self-translation, An invincible memory, in 1989. In this study, I analyse the use of the suffix -inho in a monolingual comparable corpus, in order to verify if the suffix -inho is a Brazilian linguistic-cultural characteristic by means of comparisons and contrasts in subcorpora containing Portuguese, Brazilian and English-speaking authors' literary texts translated into Portuguese. Thereby, being able to treat the use of the suffix by João Ubaldo not only as a stylistic aspect of himself, but as a peculiarity that seems to exist prominently in Brazilian Portuguese. In addition, I investigate the circulation of translated Ubaldian works, in order to observe if there were signs that motivated the realization of the second Ubaldian self-translation and to understand the linguistic-cultural implications of this circulation on the self-translated text. Finally, I compare the self-translation carried out by João Ubaldo in the bilingual parallel corpus Viva o povo brasileiro/An invincible memory with special attention to the words suffixed by -inho. This research is based on authors who describe the morphological aspects (FERRARI NETO, 2014; GONÇALVES, M. 2006; and others), on researchers who present sociocultural aspects, considering the interfaces with society, language and culture (FURTADO DA CUNHA, 2016; SOUZA, 2015; and others), on theorists who expose about stylistics (MARTINS, 2011; MONTEIRO, 2009, 2002; SIMPSON, 2004, 1997; and others), corpus linguistics (BERBER SARDINHA, 2004; VIANA, 2010, 2008; and others) and corpus stylistics (FISCHERSTARCKE, 2010), but mainly in authors who are inserted in the Translation Studies (AUBERT, 1998; GENTZLER, 2009; HEILBRON, 1999; OUSTINOFF, 2011; and others). The results, in the comparable monolingual corpus, may point out that the use of the suffix -inho is linked to the sociolinguistic-cultural behaviour of the cordial man described by Holanda (1995) as one who refrains from politeness to give way to intimacy and that, many times, it reveals itself in its sociolect through the almost unrestricted and frequent use of the suffix -inho, therefore, a Brazilian sociolinguistic-literary-cultural characteristic. In addition, the analysis may also indicate that the second self-translated Ubaldian novel occurred due to factors inherent in the circulation of other translated Ubaldian literary works. Finally, the bilingual parallel corpus has a slight numerical advantage for indirect translations compared to direct translations. Consequently, such quantifications indicate that the translation of words suffixed by -inho is more linked to a considerable change in the form and/or function of the suffix -inho in order to indicate a domestication by the self-translation. On the other hand, the numerical difference is not so disparate and, therefore, may also corroborate to a perspective that self-translation was guided by an ideology of not erasing linguistic-cultural aspects. Therewith, there is a balance between resistance and adaptation to the target language and its corresponding cultures, that is, a self-translation that seems to contain foreignization and domestication at similar levels.